Inovasi Pemberdayaan Ekonomi Kreatif Berbasis Budaya Lokal di Kabupaten Sorong Selatan - Roberth Christofel Wamaf; Zainal Fatah; Amirul Mustofah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research intends to examine the empowerment of a culture-based creative economy in South Sorong Regency as a sustainable development strategy grounded in local traditions. The primary issue identified is the lack of competitiveness for local creative goods stemming from insufficient innovation, restricted market access, and inadequate infrastructure support. This study utilizes a qualitative descriptive method through comprehensive interviews, participatory observation, and documentation with creative economy participants, traditional authorities, and local government representatives. The results indicate that innovation in the creative economy of South Sorong is achieved by enhancing the skills of local entrepreneurs, safeguarding traditional cultural crafts like carving and weaving from West Papua, and utilizing digital technology for marketing products. The local government serves as a catalyst to foster cooperation between traditional communities, educational entities, and the private sector to create a thriving creative ecosystem. The conclusion emphasizes that innovation rooted in culture is crucial for strengthening the economic resilience of communities. The research suggests creating a regional center for the creative economy to serve as a cooperative space for training, cultural production, and promotion, aimed at enhancing market networks both nationally and internationally.